CCND1 Amplification Contributes to Immunosuppression and Is Associated With a Poor Prognosis to Immune Checkpoint Inhibitors in Solid Tumors - Chen, Yu; Huang, Yingying; Gao, Xuan; Li, Yi; Lin, Jing; Chen, Lizhu; Chang, Lianpeng; Chen, Gang; Guan, Yanfang; Pan, Leong Kin; Xia, Xuefeng; Guo, Zengqing; et al. (Frontiers in Immunology, 2020)
Cyclin D1 (CCND1) amplification relevant to malignant biological behavior exists in solid tumors. The prevalence and utility of CCND1 amplification as a biomarker for the clinical response to treatment with immune checkpoint inhibitors (ICIs) are unknown. Our study is a preliminary investigation mainly focused on the predictive function of CCND1 amplification in the tumor microenvironment (TME) in the aspect of genome and transcriptome. We examined the prevalence of CCND1 amplification and its potential as a biomarker for the efficacy of ICI therapy for solid tumors using a local database (n = 6,536), The Cancer Genome Atlas (TCGA) database (n = 10,606), and the Memorial Sloan Kettering Cancer Center (MSKCC) database (n = 10,109). Comprehensive profiling was performed to determine the prevalence of CCND1 amplification and the correlation with the prognosis and the response to ICIs. A CCND1 amplification occurs in many cancer types and correlates with shorter overall survival and inferior outcomes with ICI therapy. Transcriptomic analysis showed various degrees of immune cell exclusion, including cytotoxic cells, T cells, CD8+ T cells, dendritic cells (DCs), and B cells in the TME in a TCGA CCND1 amplification population. The gene set enrichment analysis suggested that CCND1 amplification correlates with multiple aggressive, immunosuppressive hallmarks including epithelial–mesenchymal transition, transforming growth factor (TGF)-β signaling, KRAS signaling, phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling, p53 pathway, and hypoxia signaling in solid tumors. These findings indicate that CCND1 amplification may be a key point related to immunosuppression in TME and multiple malignancy hallmarks, and it hinders not only the natural host immune responses but also the efficacy of ICIs.